The neuroprotective and antioxidant profiles of selenium-containing polysaccharides from the fruit of Rosa laevigata. Issue 3 (7th March 2018) - Liu, Xuegui; Gao, Yixing; Li, Danqi; Liu, Changfeng; Jin, Mei; Bian, Jun; Lv, Mengchao; Sun, Yuqiu; Zhang, Lixin; Gao, Pinyi
Abstract : A rapid and effective approach for the extraction and separation of polysaccharides from the title fruit was developed using microwave-assisted aqueous two-phase extraction with a PEG/ammonium sulfate system. Abstract : Rosa laevigata fruit has been known as a functional foodstuff for a long time. Recently, increasing attention has been given to polysaccharides from R. laevigata fruit due to their numerous medicinal and nutritional properties. In this study, a rapid and effective approach for the extraction and separation of polysaccharides from the title fruit was developed using microwave-assisted aqueous two-phase extraction (MA-ATPE) with a PEG/ammonium sulfate system. After analysis of the response surface methodology (RSM) data based on a Box–Behnken design (BBD), a model was proposed and was found to predict an optimum yield value of 258.99 mg g −1 which is in good agreement with the experimental value (258.59 mg g −1 ). Two selenium (Se)-containing polysaccharides, Se-RLFP-1 and Se-RLFP-2, were isolated from R. laevigata fruit. Their chemical structures were elucidated by acid hydrolysis, weight-average molecular mass and Se-content analysis, along with UV, FT-IR, 1 H and 13 C NMR spectroscopy. As a result, Se-RLFP-1 was found to be mainly composed of mannose, glucose, galactose and xylose in a molar ratio of 1.4 : 7.9 : 1.0 : 1.5, while Se-RLFP-2 was composed of mannose, rhamnose, glucose, galactose and xylose (12.6 : 1.0 : 38.3 : 5.6 : 19.6). Furthermore, the antioxidant properties of the polysaccharides were investigated on the basis of FRAP, ABTS and DPPH radical scavenging assays. The results showed that the two polysaccharides had a noticeable effect on the radical scavenging of ABTS and DPPH, especially at high concentrations. In addition, the neuroprotective effect of Se-RLFP-1 and Se-RLFP-2 against oxidative stress induced by H2 O2 in SH-SY5Y neuroblastoma cells was also investigated. In particular, Se-RLFP-1 exhibited obvious neuroprotective activity at a concentration of 100 μg mL −1 .